Leibniz’s Dual Concept of Probability - Binyamin Eisner (Journal of Modern Philosophy)
Leibniz uses the concept of probability in both epistemic and non-epistemic contexts, as do many of his contemporaries. Some commentators have claimed that this dual-use is inexact or confused. In this paper, I describe Leibniz’s understanding of the concept of probability and discuss its dual usage in his work. Then, building on Leibniz’s creation theory, in conjunction with Russell’s interpretation of the Principle of Sufficient Reason, I endeavor to justify this dual usage and to show that this justification is also valuable for the contemporary discussion of the concept of probability.